TOTAL QUALITY MANAGEMENT DI INDUSTRI KECIL (STUDI KASUS PENGUSAHA INDUSTRI KECIL SEPATU CIBADUYUT) - Dede Siti Rohmah; Sri Vandayuli Riorini (Media Riset Bisnis & Manajemen, 2012)
Small enterprises play an important role in the betterment of society. Therefore, developing competitiveness of small enterprises is one of the government policies in Indonesia. In order to accomplish that goal, there is a need to know how the process of management in successful small enterprises is being done. Quality management is a way that enterprises manage their product quality. Total Quality Management (TQM) is a concept of quality management that managing the entire organization so that it excels on all dimensions of products and services that are important to the customer. A successful small enterprise is assumed implements TQM concept to build its competitive advantage.This research is aimed to elaborate how a sucessful small enterprise implements TQM in order to build its competitive advantage and was done in a sucessful small shoes enterprise in Cibaduyut Industrial Cluster Bandung.Keywords: Total Quality Management, Competitive advantage, Small industries